High incidence of clinically significant cytomegalovirus infection in CMV D+/R+ lung transplant recipients receiving 3 months of antiviral prophylaxis. Issue 4 (29th April 2019) - Kabbani, Dima; Hirji, Alim; Hernandez, Cristina; Malhi, Harjot; Mabilangan, Curtis; Chandrarathne, Sanjaya; Halloran, Kieran; Weinkauf, Justin; Kapasi, Ali; Lien, Dale; Preiksaitis, Jutta; Cervera, Carlos
Abstract: Background: Universal antiviral prophylaxis is the preferred preventive strategy for lung transplant recipients (LTRs) at risk of CMV infection. We compared the risk of CMV infection between CMV D+/R + and D‐/R + LTRs after 3 months of prophylaxis. Methods: This was a retrospective review of CMV R + LTRs transplanted between 2005 and 2013. Patients dying before completing 3 months, or receiving >180 days of prophylaxis were excluded. The primary outcome was proportion of LTRs who developed CMV infection and clinically significant CMV infection defined as CMV infection leading to preemptive therapy or CMV disease. Results: We analyzed 90 D+/R + and 72 D‐/R + with a median follow up of 730 days. CMV infection and disease was more common in D+/R + compared to D‐/R+ (CMV infection 66% vs 40%; P = 0.001; CMV disease 13% vs 4% P = 0.045). Fifty‐nine patients developed at least one episode of clinically significant CMV infection (41/90 [46%] D+/R + and 18/72 [25%] D‐/R + P =0.007) with recurrence occurring in 29 LTRs (49% of patients with previous CMV infection), of which 22 (76%) were CMV D+/R+. Thirty percent had side effects related to CMV therapy. Conclusion: Three months prophylaxis in D+/R + LTRs was associated with high rates of clinically significant CMV infection and recurrences.